EURO’ s effect on Turkish banking system and possible difficulties that appeares with EURO - Güler, Tolga (My University, 2000)
unknown
Keywords: AVRUPA BİRLİĞİ-; Bankacılık-Türkiye; Döviz; Ekonomi; EURO; Finansman ekonomisi; Para